إطلاق مصطلح أقسام الكلام للاسم والفعل والحرف عند النحويين بين القبول والاعتراض - jamal, danial; Jailani (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
Everyscientific disciplinehas special terms that characterize it. Sometimes it is found in a scientific discipline where the terms used sometimes have different meanings between one expert and another due to differences in their point of view and level of expertise. Likewise, in Nahwu science, there are several terms that differ in understanding among Nahwu scholars, either personally, in groups, or in schools of thought. Among these terms is the term